Early sowing of heat-tolerant wheat, new machinery and agronomic management enable 1.1M farmers in South Asia: Greater resilience, productivity and climate change adaptation - CGIAR Research Program on Wheat (2020)
High-yielding wheat varieties with tolerance to heat stress, in combination with systemic innovations for climate change adaptation, enabled farmers in the Eastern and Western Indo-Gangetic Plains (IGP) to sow earlier and grow their income, while reducing their environmental footprint by avoiding burning crop residue and reducing irrigation. 0.3 million farmers in Western IGP and 0.8 million in Eastern IGP practiced the innovations, achieving extra yields with less irrigation, and earning an additional income of ~US$ 200/ha.